Determination of fatigue crack growth rate from experimental data: a new approach. (5th April 2010) - Mohanty, J.R.; Verma, B.B.; Ray, P.K.
The determination of crack growth rate from laboratory observations of crack length and number of cycles is certainly a tedious job in order to considerably reduce the scatter in the test results. There are several curve-fitting methods currently in use including the standard ASTM methods. In this work, an alternative technique has been presented which has been found to be efficient in determining the crack growth rate in 2024-T3 and 7020-T7 aluminium alloy specimens.